RANCANG BANGUN SISTEM INFORMASI PENJUALAN BERBASIS WEB DENGAN FRAMEWORK CODEIGNITER PADA APOTEK ZALTA FARMA SAMARINDA KALIMANTAN TIMUR - Muhammad Irfan Permana; Purbawati Purbawati; Miftahul Huda (Journal of Sustainable Transformation, 2022)
Zalta Farma Drugstore is a health institution in selling drug. The administration system was conventional that every transaction was manually written thus causing some problems such as error in calculation, unvalidated information, and difficulties in writing report. The aims of this research were to design and to know the implementation of information system of sale product based on website at this drugstore. The development method of this system used SDLC method with application development system such as flowchart, diagram, context, DFD, and a purposed database designing (ERD). Moreover, the used Text Editor software was Visual Studio Code in PHP programming language using framework code igniter and database using MySQL. The result was an information system of sale product based on website that used by Zalta Farma Drugstore. This system helps people in transaction thus the monthly report was produced every month